Peningkatan Kompetensi Digital Guru MGMP Akuntansi Melalui Pelatihan Jaringan Komputer dan Pengolahan Data - Tata Sumitra; Safri; Peniarsih; Iswandir ZA; Muryan Awaludin; Yohannes Dewanto (Jurnal Bakti Dirgantara, 2026)
Digital transformation in school administration requires teachers to develop competencies in network technology and data processing. A needs assessment conducted among teachers of the Accounting Teachers Association (MGMP) of Jakarta Region II identified limitations in understanding basic network connectivity and the use of Microsoft Excel data analysis features. This community service program aimed to improve teachers' digital competencies through computer network and data processing training. The program was conducted on November 14–15, 2025, at Hercules Hall, Campus A, Universitas Dirgantara Marsekal Suryadarma, and involved 18 participants. The training applied a Hands-on Training approach consisting of needs assessment, material preparation, training implementation, evaluation, and mentoring. Participants' knowledge was evaluated using pre-test and post-test instruments on a 1–4 scale, while practical skills were assessed through direct observation. The evaluation results showed an increase in the average Crimping and VPN score from 2.61 to 3.55, representing a score change of 0.94. The average Pivot Table and Slicer score increased from 2.11 to 3.86, with a score change of 1.75. Practical observations indicated that participants were able to perform UTP cable crimping, use a LAN Tester, understand basic VPN configuration, and operate Pivot Table and Slicer features. The results indicate an increase in participants' knowledge evaluation scores and practical skills after completing the training.